A CAD/CAM flapless surgical technique and immediate prosthesis: a clinical report - Rogério Margonar; Thallita Pereira Queiroz; Elcio Marcantonio; Erika Oliveira De Almeida; Elcio Marcantonio Júnior (Ariesdue, 2011)
Background: This article describes a clinical report with a new system for guided surgical treatment and immediate load prosthesis in the flapless surgical technique. Case report: Based on a computed tomography (CT) of a 64 -year-old edentulous patient, the cross sections were reformatted and used to construct a virtual planning of the implants and a guide template in Dental Slice. Six dental implants were placed in the maxilla and mandible using a Slice Guide System. Following a 30-month in maxilla and 24-month in mandible healing period, the clinical and radiographic evaluation and computed tomography (CT) showed good clinical stability. The Slice Guide System proved satisfactory for the Flapless Surgical Technique in dental implants.